Synthesis and cytotoxicity test of LR-2 on breast cancer cell line T47D - Ritmaleni Ritmaleni; Dina Anitasari; Sinta Susanti; Sismindari . (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
LR-2 is a compound analog of monastrol, an anticancer agent, which has been succesfully synthesised through the application of Biginelli reaction and one of LR compound series that synthesised in Faculty of Farmacy, Universitas Gadjah Mada. This reserach was aimed to synthesized the LR-2 compound and to investigate the cytotoxicity of LR-2 on breast cancer cell line. The reaction was carried out by using the one pot reaction method. In this reaction benzaldehyde, 2-indanone and thiourea were reacted together for 6hours in acid catalyst. The cytotoxicity test was carried by using breast cancer cell line the MTT assay method and the LC50 was ditermined by using the probit analysis with Miller and Tainter method. The product was isolated by using preparative TLC in 54 % yield. The structure was elucidated by spectroscopymethods (UV-Vis, H-NMR, IR and GC-MS).The LC50 is 159 µM.Keywords : LR-2, benzaldehyde, 2-indanone, thiourea, T47D